Enhancement of Unevenly Illuminated Images: An Experiment-Based Review - Zainab Khalid Younis (Protek: Jurnal Ilmiah Teknik Elektro)
Low-lighting conditions pose significant challenges to captured images and result in degraded image quality, characterized by poor visibility, imbalanced illumination, increased noise, limited contrast, inaccurate colours, and loss of detail. In recent years, the development of effective low-light enhancement techniques has attracted considerable attention from researchers and practitioners in various fields, such as surveillance, photography, forensics, and medical imaging. This article comprehensively overviews advances in low-light image enhancement methods, techniques, and algorithms. This review summarizes the working mechanism for each reviewed algorithm, implements it, provides the results, and analyses them, highlighting the concept, advantages, and disadvantages. Overall, this review offers a comprehensive resource for researchers and practitioners interested in knowing the latest technologies and methods for low-light image enhancement. It provides insights into current challenges, promising solutions, and future directions for advancing the field of low-light imaging. Finally, it benefits various researchers by describing the available concepts, what pros to consider, and what cons to avoid when developing their algorithms.